THE STUDY OF PHYSICAL PROPERTIES AND FABRIC PROPERTIES FROM FILAGEN FIBERS MIXED PINEAPPLE LEAFS FIBERS USING NATURAL INDIGO DYED - Srivorradatpaisan, Supanicha; Khiaomang, Kriangsak; Chonsakorn, Sakorn (Srinakharinwirot University Journal of Sciences and Technology, 2022)
The objective of this research is to study physical properties of pineapple fibers and yarn, study UV resistance, antibacterial and tearing strength of hand-woven fabrics from filagen fibers with pineapple fibers using natural indigo dyed from environmentally friendly fabric by using AATCC standard test methods which provides a good dye effect. The mixing formula was 15 % pineapple fibers, 25 % filagen fibers, 60 % cotton fibers with an open-end spinning (OE) yarn spinning system to produce yarn number 20/1 Denier.Also, pineapple fabrics are able to prevent maximum ultraviolet radiation with the protection (UV-A) of 1.02% and UVB (UV-B), 0.84% which is a very good resistance to UV protection when the fabric was tested. On the other hand, non-dyed fabric is low on the level that can resist UV protection. The anti-bacterial test results found that the Staphylococcus aureus of the indigo-dyed bacteria found that the fabric has excellent antibacterial properties and can resist the Klebsiella pneumoniae type. Therefore, it was suggested that Filagen fibers with pineapple fibers has the potential in producing functional dye that could be imparted into the yarn dyeing natural indigo dye colorant system. When compared to tearing strength, the other type of woven fabric has no different warp yarn. When comparing weft yarn, there are slightly different tearing strength by pineapple fabrics with the highest tear strength.